Factor VII assay performance: an analysis of the North American Specialized Coagulation Laboratory Association proficiency testing results. Issue 3 (17th April 2013) - Zantek, N. D.; Hsu, P.; Refaai, M. A.; Ledford‐Kraemer, M.; Meijer, P.; Van, E. M.
Summary The performance of factor VII (FVII) assays currently used by clinical laboratories was examined in North American Specialized Coagulation Laboratory Association (NASCOLA) proficiency tests. Data from 12 surveys conducted between 2008 and 2010, involving 20 unique specimens plus four repeat‐tested specimens, were analyzed. The number of laboratories per survey was 49–54 with a total of 1224 responses. Numerous reagent/instrument combinations were used. For FVII > 80 or <40 U/dL, 99.5% of results (859/863) were correctly classified by laboratories as normal/abnormal. Classification of specimens with 40–73 U/dL FVII was heterogeneous. Interlaboratory precision was better for normal specimens (coefficient of variation (CV) 10.7%) than for FVII<20 U/dL (CV 33.1%), with a mean CV of 17.2% per specimen. Intralaboratory precision for repeated specimens demonstrated no significant difference between the paired survey results (mean absolute difference 2.5–5.0 U/dL). For specimens with FVII >50 U/dL, among commonly used methods, one thromboplastin and one calibrator produced results 5–6 U/dL higher and another thromboplastin and calibrator produced results 5–6 U/dL lower than all other methods, and human thromboplastin differed from rabbit by +7.6 U/dL. Preliminary evidence suggests these differences could be due to the calibrator. For FVII <50 U/dL, differences among the commonly used reagents and calibrators were generally not significant.